652 Early outcomes of an app acute checkpoint inhibitor (CPI) care clinic. (10th December 2020) - Kottschade, Lisa; Fazer, Casey; Schwecke, Anna
Abstract : Background: Checkpoint inhibitors continue to be used for a wide variety of oncologic and hematologic indications. Early recognition and intervention is crucial to prevent significant morbidity and/or mortality from immune related adverse events (irAE's). Physicians and APPs outside of hematology/oncology practices are generally not familiar with these types of side effects which may lead to treatment delays, and inappropriate management. We recently identified this as a gap in continuity of care amongst patients undergoing CPI therapy for their malignancy, and therefore developed a CPI acute care outpatient clinic, designed to meet this need. Methods: Starting April 2020, we developed an CPI focused clinic led by 3 APPs to provide outpatient irAE management 5 days a week. Three types of needs were identified: acute (within 24 hours), post hospitalization (within 48 hours of discharge), and long term follow-up (high grade irAE). Results: From April 24-August 24, 2020 our CPI clinic had a total of 50 visits (30 unique patients). Given that many patients to our practice are from > 2 hours away, as well as the constraints of the current pandemic, visits were conducted as in person, video consult (telemedicine), or phone. The most common regimens for patients were PD-1 alone (10), PD-1 + targeted (7), dual CPI (6), PD-1 + chemotherapy, and clinical trial, PD-L1 alone, PD-L1 + chemotherapy (1 each). The top three types of malignancies seen were melanoma (7), lung (6) and gynecological (4). The most common irAE referral reason was hepatitis (8), diarrhea/colitis (6) and thyroiditis (4). Only three patients (10%) required higher level care (i.e ED or admission) than was able to be provided in the clinic. Twenty-two patients (73%) required steroids as their initial treatment for irAE, with 4 patients (13%) requiring referral to other specialties. Twelve patients (40%) presented with ≥2 irAE's at the time of being seen in clinic. Conclusions: Herein we present early data from an acute care APP led CPI outpatient clinic. Most patients required initiation of steroids for their irAE, however only a small majority required higher level of care and were able to be managed as an outpatient. We acknowledge that while our cohort of patients is small, it does provide early evidence of the utility of a CPI acute care clinic and additional hypothesis generating clinical questions. Ethics Approval: This study was approved by the institutional review board at Mayo Clinic